GENDER EQUALITY ISSUES IN UZBEKISTAN - Dilnavoz Ozodovna Tadjibaeva (Web of Journals Publishing, 2025)
Uzbekistan’s efforts to ensure gender equality are aligned with international standards, and national measures have been developed to expand women’s rights and opportunities. This article highlights that ensuring gender equality is not only a matter of human rights but also crucial for economic growth and sustainable development. It analyzes issues arising from gender inequality in society, particularly stereotypes based on national traditions and culture. The study also examines the impact of “selective abortion”, which has led to an imbalance in the birth rates of boys and girls in Uzbekistan.
Keywords: Gender equality, Sustainable Development Program, equal rights and opportunities, labor rights, stereotypes, selective abortion.